Impact of Renal Impairment on Intensive Blood-Pressure–Lowering Therapy and Outcomes in Intracerebral Hemorrhage: Results From ATACH-2. (31st August 2021) - Fukuda-Doi, Mayumi; Yamamoto, Haruko; Koga, Masatoshi; Doi, Yohei; Qureshi, Adnan I.; Yoshimura, Sohei; Miwa, Kaori; Ishigami, Akiko; Shiozawa, Masayuki; Omae, Katsuhiro; Ihara, Masafumi; Toyoda, Kazunori
Abstract : Background and Objective: The clinical effect of renal impairment on intracerebral hemorrhage (ICH) is unknown. This study sought to assess whether estimated glomerular filtration rate (eGFR) affects clinical outcomes or modifies the efficacy of intensive systolic blood pressure (BP) control (target, 110–139 mm Hg) against the standard (target, 140–179 mm Hg) among patients with ICH. Methods: We conducted post hoc analyses of ATACH-2, a randomized, 2-group, open-label trial. The baseline eGFR of each eligible patient was calculated using the Chronic Kidney Disease Epidemiology Collaboration equation. The outcome of interest was death or disability at 90 days. Multivariate logistic regression models were used for analysis. Results: Among the 1, 000 patients randomized, 974 were analyzed. The median baseline eGFR was 88 (interquartile range, 68, 99) mL/min/1.73 m 2 ; 451 (46.3%), 363 (37.3%), and 160 (16.4%) patients had baseline eGFR values of ≥90, 60–89, and <60 mL/min/1.73 m 2, respectively. Compared with normal eGFR (≥90 mL/min/1.73 m 2 ), higher odds of death or disability were noted among those with eGFR values of <60 mL/min/1.73 m 2 (adjusted odds ratio [OR], 2.02; 95% confidence interval [CI], 1.25–3.26) but not among those with eGFR values of 60–89 mL/min/1.73 m 2 (OR, 1.01; 95% CI, 0.70–1.46). The odds of death or disability were significantly higher in the intensive arm among patients with decreased eGFR; the ORs were 0.89 (95% CI, 0.55–1.44), 1.13 (0.68–1.89), and 3.60 (1.47–8.80) in patients with eGFR values of ≥90, 60–89, and <60 mL/min/1.73 m 2, respectively ( p for interaction = 0.02). Discussion: Decreased eGFR is associated with unfavorable outcomes following ICH. The statistically significant interaction between the eGFR group and treatment assignment raised safety concerns for the intensive BP-lowering therapy among patients with renal impairment. Trial Registration Information: Clinicaltrials.gov identifier: NCT01176565. Classification of Evidence: This study provides Class II evidence that in spontaneous ICH, decreased eGFR identifies patients at risk of death or disability following intensive BP control.